Blue moon [videorecording (Blu-Ray)] - Reynolds, Graham, 1971- (Sony Pictures Home Entertainment, 2026)
"On the evening of March 31, 1943, legendary lyricist Lorenz Hart confronts his shattered self-confidence in Sardi's bar as his former collaborator, Richard Rodgers, celebrates the opening night of his ground-breaking hit musical Oklahoma!"--